TANDA TASHIH DAN INDUSTRIALISASI MUSHAF AL-QUR’AN - Moh. Abdul Kholiq Hasan; Hikmatul Jazila Daroini (Profetika: Jurnal Studi Islam, 2020)
This paper attempt to answer how a Mushaf publisher obtained the letter “Tanda Tashih”? And how is the influence of the letter “Tanda Tashih” Mushaf on consumer confidence in the industrialization of the Mushaf al-Qur’an ?. This field research used a qualitative descriptive method with a phenomenological approach. The results showed that the “Lajnah Pentashihan Mushaf Al-Qur’an (LPMQ)” Ministry of Religion of the Republic of Indonesia has established strict procedures and accountability in issuing the letter “Tanda Tashih” as a legal permit for the circulation of Mushaf in Indonesia. The letter “Tanda Tashih” or Circular Permit can minimize various errors in publishing the Mushaf al-Qur ʻan. All companies publishing al-Qur’an in Indonesian is obliged to comply with and follow the procedures and regulations for publishing al-Qur’an that have been established by the LPMA. The aim is to guarantee the correctness of the Al-Quran manuscripts and to give consumers a sense of trust. Surat Tanda Tashih has a far-reaching and profound influence on consumers’ confidence in buying the Mushaf of the Qur’an. The existence of the Surat Tashih letter has become one of the most important factors in the development of the industrialization of the Mushaf al-Qur ʻan in Indonesia.